Analisis Tingkat Profit Abilitas Kantin dalam Perekonomian di Nurul Islam 2 : Dalam Prespektif Syari’ah (Jurnal Manajemen Kreatif dan Inovasi, 2026)
This study aims to analyze the profitability level of the canteen at Nurul Islam 2 Islamic Boarding School and its contribution to the economy of the boarding school from a sharia perspective. The background of this study is based on the important role of Islamic boarding school business units as a source of economic independence for Islamic educational institutions. The research method used is a descriptive qualitative approach, with data collection techniques through in-depth interviews, direct observation, and documentation. The main informants of this study include the canteen manager and several students as consumers. The results of the study indicate that the canteen management has been running effectively, with a transparent financial recording system, separation of personal and operational cash, and a fair and affordable pricing strategy. The canteen's profitability level is relatively stable with an average daily income of between two and three million rupiah, and increases significantly during certain activities such as Sambangan. Business profits not only have a financial impact, but also contribute to financing the boarding school's activities and improving the welfare of students. From a sharia perspective, the economic practices of this canteen have implemented the principles of honesty (shiddiq), justice ('adl), trustworthiness, and blessings (barakah), so that it can be said that the Islamic boarding school canteen is a model of micro-economy based on sustainable Islamic values ​​and oriented towards the common good.